PENGARUH HALAL LOGO, DEVOUTNESS, AWARNESS DAN MARKETING TERHADAP COUNTRY OF ORIGIN - sabirin, Sabirin; Fahmi, Muhammad (FAKULTAS EKONOMI DAN BISNIS ISLAM, 2020)
This study aims to examine the effect of Pontianak Muslims' beliefs on the country of origin in receiving halal products from Malaysia. This research is classified into positivist research. The data source in this research is primary data. While the data collection technique used a questionnaire. The population in this study were all Muslim communities in the city of Pontianak, West Kalimantan. The sample used was purposive sampling. The analysis used is multiple regression with independent variables consisting of: (1) Halal logo, (2) Devoutness, (3) Awarness, (4) Marketing. For the dependent variable, namely Country of origin. The results showed that the Halal Logo variable had a significant effect on the Country of Origin. The Devoutness variable does not have a significant effect on the Country of Origin. The Awarness variable has a significant effect on the Country of Origin. Marketing variables have a significant effect on the Country of Origin.